Hubungan Diameter dan Jumlah Koakan Terhadap Produksi Getah Pinus di Desa Sasakan Kecamatan Sumarorong Kabupaten Mamasa - Anggun Febriani; Idris, Andi Irmayanti; Rusmidin (Pangale Journal of Forestry and Environment, 2023)
The relationship between diameter and number of cocoons in pine trees has significant relevance in the context of sap production. Tree diameter is often considered an indicator of tree size and health, while the number of cocoons, which are holes where sap is harvested, can directly influence sap production. We can see this from the diameter of the pine trees in Sasakan Village, namely 42.68 cm, which can produce 345 grams/tree. Likewise, the number of koakans on pine trees greatly influences the yield of pine sap, where there are 7 koakans/tree which can produce 448 g/tree. The number of pine trees in the sampling was 30 trees. The quantitative data collection method was carried out by measuring the diameter of the tree and recording the number of cracks on a number of pine tree samples. This research aims to explore the relationship between pine tree diameter, number of koakans and sap production in Sasakan Village, Sumarorong District, Mamasa Regency. The results of this research indicate that there is an influence of the diameter and number of cocoons on the yield of pine resin. Keywords: Pinus, Tree Diameter, Number of Trees, and Pine Sap